Internal and External Textbook Evaluation - Papadaki, Aggeliki; Karagianni, Eleni (Eximia, 2023)
The purpose of this assignment is to identify and apply some criteria with the aim of evaluating the textbook used in a particular teaching context. In the first part, there is a description of the current teaching and learning situation with reference to learners’ profile, their needs and preferences, the aims and objectives set by the official curriculum and some constraints. In the second part, there is a presentation of the textbook to be evaluated with reference to its internal and external characteristics. Then, in the third part, there is a brief literature review on textbook evaluation with reference to its phases, methods and the prioritizing criteria for it. In the 4th part, there is a presentation and justification of the textbook evaluation criteria, while in the 5th part, there is implementation of the textbook evaluation criteria. Finally, there is a conclusion, summarizing all the theoretical and practical concepts mentioned in the previous stages and presenting the final results of the particular textbook evaluation.